You're hired! : putting your sociology major to work - Joseph, Cheryl (Emerald Publishing, 2017)
Featuring conversations with more than thirty sociology majors on their career trajectories, responses from employers on why they hire sociology majors, and practical career advice, You're Hired! Putting Your Sociology Major to Work provides a comprehensive account for students on the value of a sociology major.
Keywords: Success in business.; Employees -- Recruiting.; College graduates -- Employment.; Degrees, Academic.; Sociology -- Vocational guidance.; elektronické knihy; electronic books